Whole-Genome Sequencing and Genome-Wide Studies of Spiny Head Croaker (Collichthys lucidus) Reveals Potential Insights for Well-Developed Otoliths in the Family Sciaenidae - Gan, Wu; Zhao, Chenxi; Liu, Xinran; Bian, Chao; Shi, Qiong; You, Xinxin; Song, Wei (Frontiers in Genetics, 2021)
Spiny head croaker (Collichthys lucidus), belonging to the family Sciaenidae, is a small economic fish with a main distribution in the coastal waters of Northwestern Pacific. Here, we constructed a nonredundant chromosome-level genome assembly of spiny head croaker and also made genome-wide investigations on genome evolution and gene families related to otolith development. A primary genome assembly of 811.23 Mb, with a contig N50 of 74.92 kb, was generated by a combination of 49.12-Gb Illumina clean reads and 35.24 Gb of PacBio long reads. Contigs of this draft assembly were further anchored into chromosomes by integration with additional 185.33-Gb Hi-C data, resulting in a high-quality chromosome-level genome assembly of 817.24 Mb, with an improved scaffold N50 of 26.58 Mb. Based on our phylogenetic analysis, we observed that C. lucidus is much closer to Larimichthys crocea than Miichthys miiuy. We also predicted that many gene families were significantly expanded (p-value <0.05) in spiny head croaker; among them, some are associated with “calcium signaling pathway” and potential “inner ear functions.” In addition, we identified some otolith-related genes (such as otol1a that encodes Otolin-1a) with critical deletions or mutations, suggesting possible molecular mechanisms for well-developed otoliths in the family Sciaenidae.